Backlash against the #MeToo movement: How women's voice causes men to feel victimized. (April 2022) - Lisnek, Jaclyn A.; Wilkins, Clara L.; Wilson, Megan E.; Ekstrom, Pierce D.
Three studies examined whether perceived increase in women's "voice" (i.e., being heard and taken seriously about sexual assault) contributes to perceptions of bias against men. In Study 1, both men and women who perceived women to have a greater voice related to sexual assault, perceived greater victimization of men. This relationship was stronger for relatively conservative participants. In Study 2, relatively conservative (but not relatively liberal) participants who read about #MeToo perceived greater men's victimization than those in the control condition. Study 3 examined responses to perceiving that men are victimized by #MeToo. For relatively conservative (but not liberal) men, perceptions of men's victimhood led to less willingness to work alone with a woman and less willingness to combat sexual assault (relative to a control condition). Thus, while the #MeToo movement brings awareness of issues of sexual assault, it also generates a backlash among the more conservative, and may accentuate gender disparities.